An Analysis Of The Juridical Implications of Decision No. 1301/Pdt.G/2023/Pa.Smn On The Principle of Justice In Post-Divorce Marital Property Distribution - Irawati, Melania; Karjoko, Lego; Hermawan, Sapto (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study aims to examine the application of the distribution of marital property after divorce through an analysis of Decision Number 1301/Pdt.G/2023/PA.Smn. The research focuses on the division of marital property and the extent to which theories of justice are applied in the adjudication process. This study is significant as the distribution of marital property constitutes a sensitive issue within society, where justice plays a crucial role in shaping judicial decisions. Accordingly, it is necessary to analyze the factors considered by the panel of judges in adjudicating disputes concerning the division of marital property. This research employs a normative legal research method by examining applicable laws and regulations, supported by primary, secondary, and tertiary legal materials. The findings indicate that existing statutory provisions governing the distribution of marital property have not fully fulfilled the criteria of justice for wives who bear a double burden within marriage. In this context, judges are permitted to depart from positive law by applying the principle of contra legem in order to achieve substantive justice for all parties to the marriage.